Determinantes das exportações de castanha de caju da Guiné-Bissau (1986-2011): uma análise sob a ótica do modelo de gravidade de Bergstrand - Cateia, Julio Vicente (2016)
This study aims to analyze the determinants of cashew nuts exports from Guinea-Bissau to India (1986-2011), by using the Bergstrand s (1985) gravity model. An equation was estimated using panel data (OLS-pooled) and suggests that the cashew nuts exports are negatively related to the distance between the commercial centers and positively related to the exchange rate and gross incomes and per capita incomes, which is consistent with the theoretical assumptions of gravity models and the seminal studies of the economic literature with application of these models. To consider the effect of participation of the Guinea-Bissau in international organizations, the data were stacked and separated into two periods, before (1986-1996) and after (1997-2011) integration. Accordingly, two equations were estimated. In the first period it was identified a positive relationship between exports of cashew nuts and gross income, per capita income, exchange rate and distance. In the second one, the estimated equation shows that cashew nuts exports respond negatively to the distance and to variation in per capita income and positively to changes in exchange rate and gross income